The protein expression profile of ACE2 in human tissues. Issue 7 (26th July 2020) - Hikmet, Feria; Méar, Loren; Edvinsson, Åsa; Micke, Patrick; Uhlén, Mathias; Lindskog, Cecilia
Abstract: The novel SARS‐coronavirus 2 (SARS‐CoV‐2) poses a global challenge on healthcare and society. For understanding the susceptibility for SARS‐CoV‐2 infection, the cell type‐specific expression of the host cell surface receptor is necessary. The key protein suggested to be involved in host cell entry is angiotensin I converting enzyme 2 (ACE2). Here, we report the expression pattern of ACE2 across > 150 different cell types corresponding to all major human tissues and organs based on stringent immunohistochemical analysis. The results were compared with several datasets both on the mRNA and protein level. ACE2 expression was mainly observed in enterocytes, renal tubules, gallbladder, cardiomyocytes, male reproductive cells, placental trophoblasts, ductal cells, eye, and vasculature. In the respiratory system, the expression was limited, with no or only low expression in a subset of cells in a few individuals, observed by one antibody only. Our data constitute an important resource for further studies on SARS‐CoV‐2 host cell entry, in order to understand the biology of the disease and to aid in the development of effective treatments to the viral infection. Synopsis: The protein expression profile of ACE2, suggested as host receptor for SARS‐CoV‐2, is assessed in various human organs. Notably, limited ACE2 expression is observed in the respiratory system both on the protein and mRNA level. Consistent and reliable ACE2 protein expression is found in enterocytes, renal tubules, gallbladder, cardiomyocytes, male reproductive cells, placental trophoblasts, ductal cells, eye and vasculature. ACE2 expression in the respiratory system is either absent or low in a subset of cells or individuals. The comprehensive summary of ACE expression in all major human tissues and cell types constitutes an important resource for further studies on SARS‐CoV-2 infection and host cell entry. Abstract : The protein expression profile of ACE2, suggested as host receptor for SARS‐CoV‐2, is assessed in various human organs. Notably, limited ACE2 expression is observed in the respiratory system both on the protein and mRNA level.